Environmental economics : theory and practice - Endres, Alfred (Cambridge University Press, 2011)
"This intermediate-level undergraduate textbook in environmental economics builds on the microeconomics courses students take in their first year. It intentionally does not survey the whole field or present every possible topic. Instead, there is a clear focus on the theory of environmental policy and its practical applications. Most of the applied parts of the book deal with the economics of environmental policy in the European Union and in the United States. The book combines basic environmental economic analysis, such as the internalization of externalities, with recent developments in this field, including induced technical change and coalition theory. Moreover, topics from daily policy debates such as global warming are put into economic perspective. This is done in an intelligible form for advanced undergraduate students of economics, business administration, and related fields. Each part of the book contains a set of exercises and suggested solutions"--